Environmental and genetic correlates of allocation to sexual reproduction in the circumpolar plant Bistorta vivipara. Issue 7 (1st July 2015) - Bills, John W.; Roalson, Eric H.; Busch, Jeremiah W.; Eidesen, Pernille B.
Abstract : Premise of the study: Sexual reproduction often requires more energy and time than clonal reproduction. In marginal arctic conditions, species that can reproduce both sexually and clonally dominate. Plants with this capacity may thrive because they can alter reproduction depending on environmental conditions. Bistorta vivipara is a circumpolar herb that predominately reproduces clonally, but certain environmental conditions promote higher investment in flowers (and possible sexual reproduction). Despite largely reproducing clonally, the herb has high levels of genetic variation, and the processes underlying this paradoxical pattern of variation remain unclear. Here we identified environmental factors associated with sexual investment and examined whether sexual reproduction is associated with higher levels of genetic variation. Methods: We sampled 20 populations of B. vivipara across the high Arctic archipelago of Svalbard. In each population, we measured reproductive traits, environmental variables, and collected samples for genetic analyses. These samples permitted hypotheses to be tested regarding sexual investment and ecological and genetic correlates. Key results: Increased soil nitrogen and organic matter content and decreased elevation were positively associated with investment in flowers. Increased investment in flowers significantly correlated with more genotypes per population. Linkage disequilibrium was consistent with predominant clonality, but several populations showed higher genetic variation and lower differentiation than expected. There was no geographical genetic structure. Conclusions: In B. vivipara, sexual investment is positively associated with habitat quality. Bistorta vivipara predominantly reproduces clonally, but occasional outcrossing, efficient clonal reproduction, and dispersal by bulbils can explain the considerable genetic variation and weak genetic structure in B. vivipara .